Family Counselling as Decolonization: Exploring an Indigenous Social-Constructivist Approach in Clinical Practice - Stewart, Suzanne (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
In Canada, Indigenous peoples' lives are shaped by relationships with their families. These relationships are defined by traditional Indigenous conceptions of connectedness with the earth, communities, and the many relations that occur within these contexts and are based on what is termed Indigenous ways of knowing. These relationships are also described through a concept of Western social constructivism. Social constructivism is an ideal mate for Indigenous ways of knowing in the practice of family counselling because it recognizes the importance of culture and context in understanding what occurs in human interactions when constructing knowledge based on this understanding. Indigenous ways of knowing have been of recent and growing interest to family mental health practitioners and policymakers who are seeking to support clients in decolonization processes. Family service providers who work in a Western social service or health care setting have an interest in exploring forms of sociocultural theory and practice, such as Indigenous ways of knowing, in order to address and further the practitioner-family interaction and to benefit both individuals and communities in a responsible and sustainable manner. Using current and historical literature, this article presents a summary of issues and guidelines for a hybrid approach that brings together Western and Indigenous approaches for family service workers (such as counsellors, social workers, psychologists, and psychiatrists) and a set of guidelines for practical application. Implications of how these practices can positively impact and promote community mental health in the current climate of recovery from colonialism and cultural genocide are presented.